PELAKSANAAN PENGADAAN TANAH UNTUK KEPENTINGAN UMUM BERDASARKAN PERATURAN PRESIDEN NO. 148 TAHUN 2015 (Studi Kasus Pengadaan Tanah Untuk Pembangunan Jalan Tol Di Kabupaten Boyolali) - JARWADI, JARWADI (Dinamika Hukum, 2018)
The purpose of this study is to: 1) Review and analyze the procurement of land for the public interest in the construction of highways in Boyolali district is in compliance with the legislation. 2) review and analyze the procurement of land for the public interest in the construction of highways in Boyolali district already meets the elements of equity for the holders of land rights. The method of approach in writing this is the juridical sociological. The specification of this research uses descriptive analytic. Data source use the primary data and the data of skunder. Engineering data collection using the study interview, the library and study the documents. To analyze the data, the researchers used a qualitative descriptive methods of analysis. Based on the research results obtained conclusions that: 1) the implementation of the provision of land for the public interest in the construction of highways in Boyolali Regency based on presidential regulation Number 148 Year 2015 the fourth Change of over Regulation Number 71 Year 2012 President about organizing the procurement of Land for development for the benefit of the public that is implemented through the stages: stages of development plans, notification is done through socialization Councilor. This socialization activity carried out several times until it gets approval from the Councilor. The next step is done the assessment of damages that are adapted to the conditions of the location of the land. The next step is to conduct deliberations awarding damages and determination of damages. 2) procurement of land for the construction of toll roads, Solo-Mantingan already meets the elements of fairness, it is indicated by the existence of the grant of a compensation value corresponds to the market price to the community as holder of the property rights over the land, so by the existence of the toll road construction creates happiness and sense of Justice. It is in accordance with the theory of Justice advanced by John Stuart Mill. John Stuart Mill stated that justice is aimed at the attainment of happiness. Keywords: procurement of land, public interest, the elements of Justice.